2020
DOI: 10.1101/2020.03.24.20042317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Fully Automatic Deep Learning System for COVID-19 Diagnostic and Prognostic Analysis

Abstract: 1Coronavirus disease 2019 has spread globally, and medical 2 resources become insufficient in many regions. Fast diagnosis of COVID-19, and 3 finding high-risk patients with worse prognosis for early prevention and medical 4 resources optimization is important. Here, we proposed a fully automatic deep 5 learning system for COVID-19 diagnostic and prognostic analysis by routinely used 6 computed tomography.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 19 publications
0
122
0
1
Order By: Relevance
“…The studies using small dataset (e.g., <300 patients) often showed high AUC or accuracy. However, in several studies with larger dataset (> 1000 patients) [13,83], the performance drops. Consequently, the very high accuracy of AI models in small dataset may be caused by overfitting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies using small dataset (e.g., <300 patients) often showed high AUC or accuracy. However, in several studies with larger dataset (> 1000 patients) [13,83], the performance drops. Consequently, the very high accuracy of AI models in small dataset may be caused by overfitting.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited training data of COVID-19, transfer learning using chest CT images should be a good strategy. In [83], the CNN model was first trained using lung cancer dataset including 4106 patients, and finally achieved good performance in diagnosing COVID-19. Many transfer learning models in current studies used ResNet that was pre-trained in ImageNet dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, performing CT scans as a screening method presents significant limitations, both considering the risk of radiation exposure and operator or machine-type dependence. [20] Aside from these studies, many Authors propose COVID-19 AI-powered diagnostic tools not based on CT scans data. Feng et al [17] developed and validated a diagnosis aid model without CT images for early identification of suspected COVID-19 pneumonia on admission in adult fever patients and made the validated model available via an online triage calculator that needs clinical and serological data (e.g.…”
Section: Diagnosismentioning
confidence: 99%
“…Current studies have demonstrated that arti cial intelligence could distinguish COVID-19 from other pneumonia [11,12], improve radiologists' performance in distinguishing COVID-19 from non-COVID-19 pneumonia on chest CT and provide clinical prognosis with good accuracy that can assist clinicians to timely adjust their clinical management and allocate resources appropriately [13][14][15][16][17][18][19]. However, COVID-19 is caused by SARS-CoV-2 virus, its CT manifestations resemble other types of viruses.…”
mentioning
confidence: 99%